Concurrent presentation of proliferative glomerulonephritis with monoclonal immunoglobulin deposits and light chain proximal tubulopathy: a case report and review of the literature - Jingdong Zhang; Yang Liu; Fengyan Jin; Jia Li; Hui Wang; Fuzhe Ma; Ye Jia; Jinyu Yu; Shan Wu; Shaojie Fu; Zhonggao Xu; Hao Wu (Frontiers in Medicine)
The simultaneous occurrence of proliferative glomerulonephritis with monoclonal immunoglobulin deposits (PGNMID) and light chain proximal tubulopathy (LCPT) presents a unique diagnostic and therapeutic challenge. PGNMID is characterized by monoclonal immunoglobulin deposition in glomeruli, leading to proliferative glomerular pathology, while LCPT involves monoclonal light chain deposition in proximal tubular cells, causing tubulointerstitial damage. Both conditions are classified under monoclonal gammopathy of renal significance (MGRS), but their coexistence in a single patient is exceedingly rare. This case report details the presentation of a patient with nephrotic syndrome and renal insufficiency, where renal biopsy revealed both PGNMID and LCPT. Treatment with bortezomib, cyclophosphamide, and dexamethasone achieved clinical remission and significant renal function recovery. This case emphasizes the critical role of renal biopsy in the diagnosis, particularly in the absence of detectable monoclonal proteins, and demonstrates the efficacy of targeted therapy in managing such complex renal pathologies. These findings contribute to a better understanding of MGRS and may guide future therapeutic strategies for similar cases.